Meningkatkan Keterampilan Menulis Bahasa Arab Melalui Pembelajaran PjBL di SMAIT As-Syifa Boarding School Subang - Wahyuni, Siti (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This Classroom Action Research aims to improve students' Arabic writing skills using PjBL learning at SMAIT Boarding School Subang. The researcher used 2 cycles to see the progress of students' learning to write Arabic using the Kemmis & Taggart model, namely: planning, implementation, observation, and reflection carried out in cycles 1 and 2 from August 2 - September 2 2023. The research involved class XII Science 3 students at SMAIT As Syifa Boarding School Wanareja Subang. The instruments used to collect data consisted of student activity observation sheets, interviews, and Arabic writing skills tests. The research results show that PjBL learning can improve the Arabic writing skills of class XII IPA 3 SMAIT As-Syifa Boarding School Subang students. The results of this research are supported by the application of the PjBL model in learning, adopting learning technology such as Canva to design learning media and language games for students through the features available on the Canva platform. This research needs to be developed by future researchers by involving all language skills in PTK research.